2013
DOI: 10.4081/cardiogenetics.2013.e6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Is Poorly Tolerated by Patients with Hypertrophic Concentric Cardiomyopathy Caused by Mitochondrial tRNALeu (UUR) Mutations

Abstract: Knowledge on the molecular background of mitochondrial disorders has accumulated during the past two decades, but clinical and molecular features of mitochondrial cardiomyopathies (CMPs) are only starting to be characterized. We studied the detailed cardiologic phenotype of patients with adult-onset CMPs associated with mitochondrial DNA (mtDNA) mutations and their relatives, from three families. We identified a pathogenic T3258C point mutation of mtDNA tRNALeu(UUR) in an adult patient with mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our echocardiographic analysis showed that rapa treatment decreased left ventricular mass in both WT and Deletors, but did not affect the functional parameters (Figure S3F). Deletors showed a tendency to slight hypertrophy of the interventricular septum in both systole and diastole, a typical sign in some mitochondrial disease patients, increasing their risk of arrhythmia complications (Heliö et al, 2013). Rapa cured this septum hypertrophy (Figure S3F).…”
Section: Cardiac Septum Hypertrophy Improved By Mtorc1 Inhibitionmentioning
confidence: 94%
“…Our echocardiographic analysis showed that rapa treatment decreased left ventricular mass in both WT and Deletors, but did not affect the functional parameters (Figure S3F). Deletors showed a tendency to slight hypertrophy of the interventricular septum in both systole and diastole, a typical sign in some mitochondrial disease patients, increasing their risk of arrhythmia complications (Heliö et al, 2013). Rapa cured this septum hypertrophy (Figure S3F).…”
Section: Cardiac Septum Hypertrophy Improved By Mtorc1 Inhibitionmentioning
confidence: 94%
“…Our findings support the hypotheses that a high mtDNA mutation load alone is not sufficient to trigger clinical heart disease in mtDNA disease patients; but, other adaptative metabolic pathways, either expose or protect the patient from cardiac manifestations. Currently, due to the severity of the heart symptoms, regular cardiac follow-ups are recommended for all m.3243A>G patients [ 37 ]. Understanding these additional factors would aid in early identification of those patients that will develop heart defects.…”
Section: Discussionmentioning
confidence: 99%